First record of Alternatipathes bipinnata (Cnidaria: Antipatharia) in the Southern Hemisphere - Francisco Araya, Juan; Aliaga, Juan Antonio; Opresko, Dennis (Zootaxa, 2017)
Antipatharians are still poorly documented in the southeastern Pacific, with just eleven species reported in Chilean waters, all of them distributed in subtidal areas from 70 to 2000 m depth (Häussermann & Försterra, 2007; Cañete & Häussermann, 2012; Araya et al. 2016a). Among the family Schizopathidae Brook, 1889, which is characterized by polyps elongated in the direction of the axis and having a transverse diameter of 2 mm or more (Opresko, 2002), the recently described deep-water genus Alternatipathes Molodtsova & Opresko, 2017, encompasses two recognized species, Alternatipathes alternata (Brook, 1889), reported from abyssal basins (2670 to 5089 m depth) of the Indian and Pacific Oceans, and Alternatipathes bipinnata (Opresko, 2005), known from a few specimens collected in deep waters (1130 to 2846 m) off the Pacific coasts of northern Mexico and southern USA (Opresko, 2005; Molodtsova & Opresko, 2017).